3D printing of cellulose nanocrystals based composites to build robust biomimetic scaffolds for bone tissue engineering - Kanga Marius N’Gatta; Habib Belaid; Joelle El Hayek; Edja Florentin Assanvo; Marilyn Kajdan; Nathalie Masquelez; David Boa; Vincent Cavaillès; Mikhael Bechelany; Chrystelle Salameh (Scientific Reports, 2022)
Abstract Cellulose nanocrystals (CNC) are drawing increasing attention in the fields of biomedicine and healthcare owing to their durability, biocompatibility, biodegradability and excellent mechanical properties. Herein, we fabricated using fused deposition modelling technology 3D composite scaffolds from polylactic acid (PLA) and CNC extracted from Ficus thonningii. Scanning electron microscopy revealed that the printed scaffolds exhibit interconnected pores with an estimated average pore size of approximately 400 µm. Incorporating 3% (w/w) of CNC into the composite improved PLA mechanical properties (Young's modulus increased by ~ 30%) and wettability (water contact angle decreased by ~ 17%). The mineralization process of printed scaffolds using simulated body fluid was validated and nucleation of hydroxyapatite confirmed. Additionally, cytocompatibility tests revealed that PLA and CNC-based PLA scaffolds are non-toxic and compatible with bone cells. Our design, based on rapid 3D printing of PLA/CNC composites, combines the ability to control the architecture and provide improved mechanical and biological properties of the scaffolds, which opens perspectives for applications in bone tissue engineering and in regenerative medicine.